2013
DOI: 10.1002/j.2161-0045.2013.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Research in Career Counseling and Development—2012

Abstract: This annual review of the 2012 career development/vocational psychology literature includes 191 empirical (69%) and conceptual (31%) articles from career, counseling, development, and international journals. The review is divided into 4 major areas: professional issues, work and well‐being, life‐span perspectives, and career theory and concepts. Subsumed within these clusters are foci on the status of career/vocational guidance around the globe, the career development experiences of immigrants, and the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 218 publications
0
7
0
Order By: Relevance
“…Content analyses of journal articles take four basic forms. The first involves analyzing the content of multiple journals in career development in a given year, such as those published in CDQ , beginning with Savickas's 1988 review (Savickas, ) and continuing through Bikos et al's 2012 review (Bikos et al, ), as well as annual analyses of content in JVB (Fitzgerald & Rounds, ). The second involves analyzing the content of a single journal over an extended period of time, such as that of CDQ (Buboltz & Savickas, ; Loveland et al, ) or that of JCA (Whiston, Rose, Peterson, & Nguyen, ).…”
Section: Content Analyses Of Journal Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Content analyses of journal articles take four basic forms. The first involves analyzing the content of multiple journals in career development in a given year, such as those published in CDQ , beginning with Savickas's 1988 review (Savickas, ) and continuing through Bikos et al's 2012 review (Bikos et al, ), as well as annual analyses of content in JVB (Fitzgerald & Rounds, ). The second involves analyzing the content of a single journal over an extended period of time, such as that of CDQ (Buboltz & Savickas, ; Loveland et al, ) or that of JCA (Whiston, Rose, Peterson, & Nguyen, ).…”
Section: Content Analyses Of Journal Articlesmentioning
confidence: 99%
“…The number of articles and journals represented in the reviews has grown over time. Each one of those 25 reviews provided a brief summary of the content of articles by topic, as well as a commentary on the nature of the literature published that year (Arbona, 2000;Bikos, Dykhouse, Boutin, Gowen, & Rodney, 2013;Chope, 2008;Cook, 1991;Creager, 2011;Dagley & Salter, 2004;Erford & Crockett, 2012;Flores et al, 2003;Guindon & Richmond, 2005;Harrington & Harrigan, 2006;Hartung, 2010;Jepsen, 1992;Luzzo & MacGregor, 2001;Niles, 1997;Patton & McIlveen, 2009;Salomone, 1993;Savickas, 1989;Spokane & Hawks, 1990;Stoltz-Loike, 1996;Subich, 1994;Swanson & Parcover, 1998;Tien, 2007;Walsh & Srsic, 1995;Whiston & Brecheisen, 2002;Young & Chen, 1999). In reviewing past CDQ annual reviews, we identified some noteworthy trends.…”
mentioning
confidence: 99%
“…Previous career counseling often serviced individuals faced with career dilemma, such as those people swaying in the career transition and those with low career self-efficacy (Bikos et al, 2013 ). LDC attempts to help individuals discover the life theme from the narrative process and build and create careers in the long run, not just focus on the current career challenges.…”
Section: Life Design Counselingmentioning
confidence: 99%
“…In the annual review of the 2012 career guidance/career development/vocational psychology literature, the conclusion is that mixed-method approaches constitute 6 % of the research articles published (Bikos, Dykhouse, Boutin, Gowen, & Rodney, 2013). The quantitative approaches constitute 53 %.…”
Section: Mixed Methods Approaches As a Research Strategy To Support Evmentioning
confidence: 99%